Ensuring and restrictinghuman rights and freedoms under martial law in Ukraine - Galagan, Olexandr; Drozd, Valentyna; Galagan, Sergii; Drozd, Vitalii (DIXI, 2023)
Human rights protection in every society is a fundamental tool in the preservation and conservation of a democratic society. It therefore becomes the responsibility of every state in ensuring that those constitutional values protecting its citizens should be respected without any instances of violations. This issue of protection has become more of a nightmare and frustrated as we always experience violations of fundamental human rights of people, in which the case of Ukraine is not an exception with the presence of martial law. This article articulates that it becomes the place of the state of Ukraine in ensuring that those constitutional bases of human rights freedoms should be respected without any aspect of violation and restriction. For the situation is complex and questionable when there is continuous violation of human rights and freedoms with the constitutional bases restricting violations. In answering the various worries and controversies surrounding the protection of human rights in Ukraine under the martial law system, it will be proper for us in adopting a philosophical method so as in determining the rationale and the reasons behind aspect of restricting human rights and freedoms under the martial law in Ukraine. From the above explanation, the rule remains that the present of the martial law in Ukraine is more a curse than a blessing as human rights violations continue to be on the increase defeating the original intention of the law being that of the conservation and preservation of all human rights values and dignities in the country. This is really frustrating and embarrassing as human values are rather degrading and pathetic instead of the expectations and standards stipulated by the law of the country. It is really an aspect of disappointment.
Keywords: human rights; martial law; restricting; Ukraine; ensuring